2003
DOI: 10.1002/jez.b.45
|View full text |Cite
|
Sign up to set email alerts
|

ARNT gene multiplicity in amphibians: Characterization of arnt2 from the frog Xenopus laevis

Abstract: The aryl hydrocarbon receptor nuclear translocator (ARNT) is a member of the Per‐ARNT‐Sim (PAS) protein superfamily, transcription factors that mediate the cellular responses to various developmental signals and environmental conditions. A β‐class (“partner”) PAS protein, ARNT exhibits the capacity to form transcriptionally active heterodimers with several α‐class (“sensor”) proteins, including the aryl hydrocarbon receptors (AHRs), the hypoxia‐inducible factors (HIFs), and the Single minded (Sim) proteins. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
14
1
Order By: Relevance
“…Although previous research has shown X. laevis embryos express both ARNT1 and ARNT2 [24], we detected low or minimal expression of the latter gene in this kidney epithelial cell line. This is in contrast to mammals, which express ARNT2 in kidney [26, 27], as well as some fish, which express ARNT2 ubiquitously [28].…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…Although previous research has shown X. laevis embryos express both ARNT1 and ARNT2 [24], we detected low or minimal expression of the latter gene in this kidney epithelial cell line. This is in contrast to mammals, which express ARNT2 in kidney [26, 27], as well as some fish, which express ARNT2 ubiquitously [28].…”
Section: Resultscontrasting
confidence: 94%
“…The Xenopus laevis AHR pathway contains two AHR paralogs (AHR1α and AHR1β; [11]), two ARNTs (ARNT1 and ARNT2 [23, 24]), and two CYP1As (CYP1A6 and CYP1A7 [25]). To confirm the expression of these key pathway components in the previously uncharacterized cell line, XLK-WG, cells grown to near confluence were treated with 100 nM TCDD or DMSO vehicle and total RNA was harvested after 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…X. tropicalis has one AHR gene, while X. laevis has two AHR1s (AHR1α and AHR1β) (Ohi et al , 2003; Lavine et al , 2005). At least two ARNT genes occur in X tropicalis (ARNT1, ENSXETG00000024204, and ARNT2) and X. laevis (ARNT1 and ARNT2) (Rowatt et al , 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported for AHR1α and AHR1β in X. laevis, which displayed increasing expression levels from stages 12 to 54, with a temporal drop in the period around hatching, and a peak at stage 48 (Lavine et al , 2005). We did not examine gene expression before hatching but this has been studied in X. laevis , where the earliest expression of CYP1A7 , AHR1β, and ARNT2 was detected at stages 12, 14, and 22, respectively (Ohi et al , 2003; Rowatt et al , 2003; Lavine et al , 2005). …”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, The results of (Prasch et al, 2004) show that zebrafish ARNT2 is not essential for mediating TCDD developmental toxicity in zebrafish and suggest that alternate dimerization partners exist for zfAhR2 in vivo, and further proved by (Antkiewicz et al, 2006); furthermore, Prasch et al (2006) confirmed that zebrafish ARNT1 play an essential role in mediating TCDD developmental toxicity, whether the expression pattern of ARNT genes is especial for zebrafish, further study of this interesting protein is eagerly awaited; while a different ARNT, likely an ARNT1 predominates in rainbow trout and scup (Powell and Hahn, 2000). Interestingly, however, the recently sequenced Fugu rubripes genome appears to encode two forms of ARNT (Rowatt et al, 2003) suggesting that, at least in some fish species, two ARNT genes do exist.…”
Section: Heterodimerization Of Ahrmentioning
confidence: 82%